Maturation of membrane-bound hydrogenase of Alcaligenes eutrophus H16. - Kortlüke, C (1992)
The formation of the catalytically active membrane-bound hydrogenase (MBH) of Alcaligenes eutrophus H16 requires the genes for the small and large subunits of the enzyme (hoxK and hoxG, respectively) and an accompanying set of accessory genes (C. Kortl ke, K. Horstmann, E. Schwartz, M. Rohde, R. Binsack, and B. Friedrich, J. Bacteriol. 174:6277-6289, 1992). Other genes located in the adjacent pleiotropic region are also required. In the absence of these genes, MBH is synthesized but is catalytically inactive. Immunological analyses revealed that cells containing active MBH produced the small and large subunits of the enzyme in two distinct conformations each; only one of each, presumably the immature form, occurred in cells devoid of MBH activity. The results suggest that the conversion of the two subunits into the catalytically active membrane-associated heterodimer depends on specific maturation processes mediated by hox genes.